Citizen Perception of Green Spaces Prioritization in Urban Kenya: The Case of Kisumu City and Eldoret Municipality - Ng’etich, J.; Kiplagat, A.; Khazenzi, J.; Odhiambo, K.; Lagat, M. J. (Africa Environmental Review Journal, 2022)
Kenya is currently experiencing rapid rate of urbanization which is considered as one of the highest in the region, with over 30% of its population living in urban areas. It is projected that by 2050 Kenya will be predominantly an urban nation as half of its population will be living in cities and urban areas. This underscores the need for urban planners and managers to address themselves to the issues of provision of physical and socio-economic infrastructure services to match population growth, one of them being planning for green spaces. Green spaces are sacrosanct as they satisfy the socio-economic and environmental demands of urban dwellers. Availability of green spaces is considered as an indicator of measuring sustainable cities, smart cities and urban resilience. The Kenyan Urban planning norms recognizes sufficient availability of green spaces as a criterion for classification of cities and urban areas. Using case studies of Kisumu city and Eldoret Municipality, the study was aimed at examining the perceptions of citizens on green spaces planning. The study is underpinned by basic needs theory which informs ranking of priority needs of communities. A total of 1030 users of green spaces who visited seven green spaces in Kisumu City and two green spaces in Eldoret Municipality were randomly selected for interviews with the purpose of soliciting data on their views on the place of green spaces according to their felt needs. Based on frequency analysis, 28% of respondents indicated that education should be put as the first priority, followed by job creation in industrial areas (23%), and housing provision in residential areas (21%). Provision of water and sanitation services (10%),improvement of business environment(7%),and transport infrastructure (5%) ranked fourth, fifth and sixth respectively while 4% of the Respondents ranked both provision of green spaces and public purposes to be in the seventh and the last position in their scheme of priorities .The study concludes that green space planning is not considered as an immediate need by citizens in urban Kenya, and hence the need for planners and urban managers to initiate urban planning forums to enlighten citizens on the value of green spaces.